Aesthetic Earlobe Reduction: A Practical Geometric Modification with Natural Contour Preservation - Tatar, Sedat; Sezgin, Billur (Facial Plastic Surgery, 2019)
Earlobe elongation is one of the signs of aging process and surgical correction is warranted for earlobe ptosis. Most of the earlobe reduction techniques result with scars on the anterior or inferior aspect of the earlobe or unnatural appearance. The authors present a modified technique for earlobe reduction and reshaping that results with an acceptable scar set on the natural groove of the anterior surface of the earlobe. Nine healthy female patients were operated for earlobe reduction. The postoperative and preoperative otobasion inferius (O)–subaurale (S) distances of these patients were evaluated. According to the measurements, the preoperative mean O–S distance of the right lobule was 13.1 ± 1.8 mm and the left lobule was 12.8 ± 1.9 mm, while the postoperative O–S distance of the right side was 3.4 ± 1 mm and the left side was 3.4 ± 0.7 mm (Table 2). This translated to an approximate pre- and postoperative O–S distance difference of 9 mm, a significant reduction that resulted with ideal O–S values. The presented approach has numerous advantages including inconspicuous scarring, smooth lateral earlobe contours, and undisturbed free borders. This was a Level IV therapeutic study.
Keywords: earlobe; earlobe reduction; earlobe ptosis; earlobe reshaping; earlobe surgery